Sircular Migrant Livelihood Adaptation Informal Sector in Gorontalo City - Sri Endang Saleh; Syarwani Canon (AIBPM Publisher, 2018)
This study purpose to examine the adaptation strategies of circular migrant livelihoods that working in the informal sector. The research location in Pasar Sentral Gorontalo City, using descriptive research methods. The study sample is 30 peoples were circular migrants who carried out their business activities in the informal sector by convenience samples. Data collection with direct observation, questionnaire, in-depth interview, and documentation recorded. The results of this study indicate that the process of adaptation of circular migrants in the informal sector of the Pasar Sentral in Gorontalo City has occurred since circular migrants have migrated. Circular migrant community networks have a very large role in helping new migrants, generally from the same region. These circular migrants were invited by friends and relatives who had succeeded in becoming traders in the Pasar Sentral in Gorontalo City. The first time that to get a job is to apply directly by going to the merchant alone and asking to be hired. Livelihood strategies carried out by the Informal Sector Circular Migrants, namely survival strategy, debt, and network utilization. Socio-economic changes can be seen from the improvement in the economic level of circular migrant households with an increase in income, an increase in capital ownership and a change in the quality of ownership of house buildings. Keywords: Circular migrants, adaptation, livelihood strategy